Hubungan Status Gizi dan Anemia pada Ibu dengan Kejadian BBLR di RSUD Dr. R. Soedjono Selong - Siti Naili Ilmiyani; Yusuf, Nurlathifah N.; Aprianti, Nurannisa Fitria (STIKes Hamzar, 2021)
Background: In terms of mortality of 60-80% of neonatal deaths caused by low birth weight, because the lbw 20 times higher risk of death in infancy. Malnutrition and anemia lead to low birth weight. The number of pregnant women anemia in bantul regency (36.6%) and nutritional status are event numbers (4.9 percent). Objective : This research is a survey research study design with analytic case control. The sample in this research is an experienced maternity mother lbw and not lbw as much as 246 cases, groups of cases (lbw) 123 and 123 cases of the control group. Analysis of the data used is the test of chi square and multivariate analysis with multiple linear regrasi. Methods: Analysis of the results obtained, that there is no significant relationship between nutritional status with the incident with the highest p 0,236 low birth weight and there is no significant relationship between anemia and lbw with the occurrence value p 0,290. Result :There is no relationship of nutritional status and anemic, but the nutritional status and risk factors for the onset of anemia is a low-value odds ratio 2,070 on nutritional status and 1,324 for anemia. Conclusion: More expectant mothers are expected to be improved again in an effort to consume fe tablets for didn't happen anemia and increased nutritional needs during pregnancy to prevent low birth weight.